What triggered massive hemoptysis in Goodpasture syndrome with isolated pulmonary involvement in a 14-year-old boy? - Tuğba Şişmanlar-Eyüboğlu; Ayşe Tana Aslan; Deniz Gezgin-Yıldırım; Necla Buyan; Serhat Emeksiz; Gökhan Kalkan (The Turkish Journal of Pediatrics)
Goodpasture syndrome is a rare, autoimmune disease associated with the development of antibodies against a specific antigen both in glomerular basement membrane and alveolar basement membrane. It is very rare in childhood and its incidence is not known. Although the mechanism of the disease is the same in lung as in the kidney, sometimes it presents with involvement of only one organ. Pulmonary involvement may be lifethreatening in patients with massive hemoptysis. Herein we report a 14-yearold boy with isolated lung involvement. He had massive hemoptysis following bronchoscopy and recovered succesfully with treatment.